2003
DOI: 10.1053/jlts.2003.50043
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte antigen–C in short- and long-term liver graft acceptance

Abstract: In liver transplantion, rejection is still an important problem, and the role of human leukocyte antigens (HLA) has not been clearly established. At present, the possible involvement of HLA-C antigen in liver transplantation is still unexplored. The aim of this work was to analyze the influence of HLA-C polymorphism on the outcome of liver transplantation. For this purpose, genotyping of 100 orthotopic liver transplant recipient-donor pairs for HLA-C was performed with polymerase chain reactionsequence-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 49 publications
3
15
0
Order By: Relevance
“…Indeed, this effect appears independent of HLA-AϩBϩC class I mismatching, as well as from the most frequent liver diseases, as well as age and gender (data not shown). The present data partially agree with those previously obtained by us in a shorter series of liver transplants [14], and appear to support the influence of the liver recipient's HLA-C genotype in the early success of the liver graft. However, they do not definitely confirm the previously suggested deleterious effect of the HLA-Cw*06 allele for liver graft acceptance.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, this effect appears independent of HLA-AϩBϩC class I mismatching, as well as from the most frequent liver diseases, as well as age and gender (data not shown). The present data partially agree with those previously obtained by us in a shorter series of liver transplants [14], and appear to support the influence of the liver recipient's HLA-C genotype in the early success of the liver graft. However, they do not definitely confirm the previously suggested deleterious effect of the HLA-Cw*06 allele for liver graft acceptance.…”
Section: Discussionsupporting
confidence: 92%
“…Moya-Quiles et al [37] demonstrated that OLT recipients without acute rejection episodes had fewer HLA-Cw*06 alleles than those with acute rejection episodes, or the controls, and also observed that the frequency of acute rejection episodes decreased when there were fewer HLA-C mismatches. The same group reported that graft survival rates increased when there were fewer mismatches in both HLA-C and NK alloantigens [38]. In our cohort of OLT patients, there was no significant difference in survival between those with and without NK alloreactivity potential.…”
Section: Discussionsupporting
confidence: 38%
“…There have been conflicting reports on the impact of KIR genes and KIR-ligand matching in LT [910111213]. KIR-ligand mismatches might induce recipient NK alloreactivity toward the liver allograft, resulting in a negative effect on the graft.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies utilized several KIR models such as KIR gene-gene mismatch, HLA-C genotype mismatch, and KIR-ligand mismatch for donors lacking ligands for inhibitory KIR, which present in recipients [589]. In liver transplantation (LT), previous studies reported the impact of HLA-C allotypes on acute rejection (AR) and graft survival [910111213], but some studies demonstrated no effect on graft outcomes [14]. In addition, most previous studies for HLA-C, KIR genotypes, or KIR-ligand matching in LT do not report Asians as a separate group, and no data has been acquired previously for Korean liver transplants.…”
Section: Introductionmentioning
confidence: 99%